THE CONDITION AND STRUCTURE OF THE CORRUPTION IN THE RUSSIAN UNIVERSITIES - Svetlana S. Donetskaya (Высшее образование в России, 2016)
The corruption has covered almost all economic sectors and levels of government in modern Russia. The education sector has a third place in the corruption rating. The higherpositions in this rating belong to officials and police structures. The third part of all cases of bribe-taking in the education sector pertain to universities. However there are no proper investigations of this process.This paper presents an analysis of the bribery level in Russian universities based on the student’s views investigation. The corruption level at the universities in different federal districts of Russian Federation is shown taking into account the areas of education and the date of the universities founding. The author discusses the reasons of the corruption in the Russian universities.